1994
DOI: 10.1095/biolreprod51.3.551
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Populations of the Adult Rat Testis Following Removal of the Leydig Cells by Treatment With Ethane Dimethane Sulfonate and Subcutaneous Testosterone Implants1

Abstract: The influence of the Leydig cells on the leukocyte population of the testis was investigated. Leydig cells were destroyed by ethane dimethane sulfonate (EDS) treatment in adult male rats, with or without low-dose s.c. testosterone implants to prevent Leydig cell recovery. Leukocytes were counted in perfusion-fixed frozen testis sections, by use of cell-specific monoclonal antibodies (mAbs) with immunoperoxidase detection, or toluidine blue staining. The majority (81%) of testicular leukocytes (OX1+) were immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
118
2
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 48 publications
6
118
2
3
Order By: Relevance
“…The volume densities of macrophages in the rat liver and testis, as determined by stereological and other analysis, are similar (6,35,68). Although there is some evidence that the liver itself possesses a degree of immunological protection against graft rejection, based on the relative success rates for transplantation of this organ (9), it is nonetheless clear that the proinflammatory response of the testis is severely compromised relative to the liver.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The volume densities of macrophages in the rat liver and testis, as determined by stereological and other analysis, are similar (6,35,68). Although there is some evidence that the liver itself possesses a degree of immunological protection against graft rejection, based on the relative success rates for transplantation of this organ (9), it is nonetheless clear that the proinflammatory response of the testis is severely compromised relative to the liver.…”
Section: Discussionmentioning
confidence: 95%
“…The testicular artery on one side was clamped, and the ipsilateral testis was collected, snap-frozen, and stored at Ϫ70°C for protein extraction. The remaining testis was perfused with saline by whole-body perfusion via the descending aorta, followed by periodate-lysine-paraformaldehyde fixative (ϳ10 -15 min), as previously described (68). The perfused testis was collected, postfixed in periodate-lysine-paraformaldehyde solution for a further 3 h, followed by immersion at 4°C in 7% sucrose for 36 h, then snap-frozen in liquid nitrogen, and embedded in Optimal Cutting Temperature (OCT) compound (Tissue-TEK, Elkhart, IN).…”
Section: Experimental Procedures Experiments 1: Lps Dose and Extended mentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the administration of T3 implant as expected resulted in the reduction of serum gonadotropin levels below those necessary to sustain spermatogenesis. In contrast, the higher-dose T24 implants cause supraphysiological serum concentrations and resulted in sufficient levels (10-40% of normal testicular levels) to support qualitatively normal seminiferous tubule function (40,45,46). The histological assessment of the treated animals clearly showed that testosterone replacement provided a significant degree of protection against the development of orchitis with only 17% of EAO+T3 and 33% of EAO+ T24 animals developing the disease, compared with 80% when no hormone intervention was performed.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, high-dose T24 similarly causes a drop in LH, but supplies sufficient testosterone to maintain intratesticular T levels adequate to support qualitatively normal seminiferous tubule function (38,40).…”
Section: Induction Of Eao and Testosterone Replacement Treatment (Expmentioning
confidence: 99%